Natural Resource Abundance, Institutions and Economic Growth in Africa (2015)
The study analysed the effect of institution on resource curse abundance-economic growth nexus using the system generalised method of moments. The empirical results refute the resource curse hypothesis in Africa. In addition, institutions have dampening effect on the nexus. This stems from the fact that the institutional development level of most African countries is weak. The study also found out that the resource curse hypothesis is not peculiar to oil wealth as indicated in the literature. Lastly, our results do not support the rentier effect as a possible channel of the hypothesis.